Characterization and phylogenetic relationships of strains of Dengue type 1 virus from Costa Rica - Cerdas Quesada, César Alonso (2007)
Phylogenetic analysis of the envelope gene sequence (E) of three isolated Dengue virus type 1 (DEN- 1) sequences from the Costa Rican 1993 epidemic was performed. All the strains fell into genotype V. Genotype V has grouped all the strains isolated from America, three strains from Africa and two strains from Asia. Costa Rican strains are closely related to the strain from Angola and to the Brazil 1990 strain. Costa Rican strains are able to cause DHF but with low clinical disease severity and low incidence maybe because of low virulence.